A Collaborative Approach to Reduce the Spread of COVID-19 in a Large Urban Hospital in South Florida - David Schneider; Roberto L. Roman Laporte (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2020)
The novel Coronavirus has proven challenging for many healthcare organizations. Hospitals are pressed to secure sufficient personal protective equipment to ensure the safety of their healthcare personnel and various strategies have been implemented to stop the spread of the virus. There are still many unknowns about COVID-19 and hospitals are rapidly adapting to new information while trying to maintain the safety and wellbeing of healthcare personnel. Baptist Hospital of Miami developed a collaborative data driven plan to monitor, disseminate vital information, and implement various strategies to protect employees and patients during the pandemic.